IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION VALUES IN FORMING YOUNG ENTREPRENEURS (STUDY AT NU SUNAN AMPEL PONCOKUSUMO VOCATIONAL SCHOOL) (International Journal of Education and Literature, 2022)
The large number of young people's interest in entrepreneurship needs to get support and facilities, one of which is through entrepreneurship education. In entrepreneurship education, entrepreneurial values ​​are taught as a value that must be upheld in running entrepreneurship. The purpose of this study was to determine entrepreneurial learning at SMK NU Sunan Ampel Poncokusumo, the values ​​of entrepreneurship education at SMK NU Sunan Ampel Poncokusumo, and the values ​​of entrepreneurship education at SMK NU Sunan Ampel Poncokusumo to form young entrepreneurs. This study uses a qualitative case study approach, using interviews, observation, and documentation. The research results show thatPKK subjects at SMK NU Sunan Ampel Poncokusumo are divided into 2, namely Entrepreneurship PKK and Productive PKK, Entrepreneurship PKK studies entrepreneurship in theory and Productive PKK is practice. Entrepreneurial values ​​in subjects on PKK Entrepreneurship learning valuesIndependent, Creative, Honest, Discipline, Responsibility, Cooperation, and Communicative are taught in theory while in Productive PKK Creative values, dare to take risks, action oriented, hard work, honest, innovative, cooperation, realistic, curiosity, and Communicative skills are taught through practice. Through entrepreneurial values ​​that are implemented in learning, PKK is able to encourage students to start entrepreneurship from an early age, this is also driven by the many practical experiences students gain